Architecture of NaFe(MoO4)2 as a novel anode material for rechargeable lithium and sodium ion batteries - Tamboli, Asiya M.; Tamboli, Mohaseen S.; Praveen, C. S.; Dwivedi, Pravin Kumari; Karbhal, Indrapal; Gosavi, Suresh W.; Shelke, V, Manjusha; Kale, Bharat B. (Applied Surface Science, 2021)
In recent decades, particular focus has been given to enhance the capacity of LIBs and SIBs either by developing new materials or by modifying existing materials. Hence, we have demonstrated a new anode material i.e. sodium iron molybdate [NaFe(MoO4)2] for both LIBs and SIBs. NaFe(MoO4)2 has been successfully synthesized by solid-state combustion technique and tested as a promising new anode material for both LIBs and SIBs. A detailed analysis of the crystal structure has been performed using DFT calculations. NaFe(MoO4)2 crystallizes in the monoclinic phase with the space group C2/c (#15). FESEM also shows highly crystalline monoclinic shaped crystals of micron size. When evaluated as an anode material for LIBs, NaFe(MoO4)2 electrode exhibited electrochemical capacity of 920 mAhg- 1 in the second cycle at the current density of 50 mAg-1. Though capacity decreases on further cycling, the coulombic efficiency was maintained at 99% for 50 cycles. Significantly, a high discharge capacity of 100 mAhg- 1 was maintained at a very high rate of 1 Ag-1. On the other hand, we have also tested NaFe(MoO4)2 for SIBs which shows excellent reversible specific capacity i.e. 100 mAhg- 1 at the current density of 100 mAg-1 even after 500 cycles. This novel system has shown good stability for LIBs and SIBs which is hitherto unattempted.
Keywords: Electrochemical study; lithium-ion battery; Morphology; NaFe(MoO4)2; Sodium-ion battery

Engineering microstructure of LiFe(MoO4)(2) as an advanced anode material for rechargeable lithium-ion battery - Tamboli, Asiya M.; Tamboli, Mohaseen S.; Dwivedi, Pravin Kumari; Praveen, C. S.; Karbhal, Indrapal; Shelke, V, Manjusha; Kim, Bomyung; Park, Chinho; Kale, Bharat B. (Journal of Materials Science-Materials In Electronics, 2021)
Graphite is considered as an ideal anode material for lithium-ion battery (LIB) due to its high stability, good conductivity and wide source of availability. However, the low energy density and theoretical capacity of graphite cannot meet the needs of high performance anode materials. To circumvent this issue, alternative materials have been sought for many years now. Herein, we report the synthesis of highly crystalline lithium iron molybdate LiFe(MoO4)(2) by combustion method and evaluated its performance as an anode material for lithium-ion batteries. Triclinic LiFe(MoO4)(2) crystals having particle size 2-5 mu m with good crystallinity were obtained. The material shows long cycle life and high rate performance than commercial graphite and exhibits first reversible discharge capacity of 931.6 mAh/g at a current density of 100 mA/g which is three times higher than commercial graphite. The high specific capacity together with the outstanding rate and cycle performance makes LiFe(MoO4)(2) a promising anode material for LIB. A detailed analysis on the crystal structure and electronic properties of LiFe(MoO4)(2) is presented based on DFT studies to complement the experimental observations.

Green synthesis of GO-loaded Ag/ZnO nanocomposites for methyl orange degradation - Nadargi, Digambar Y.; Nadargi, Jyoti D.; Tamboli, Mohaseen S.; Tamboli, Asiya M.; Mulla, Imitaz S.; Umar, Ahmad; Truong, Nguyen Tam Nguyen; Suryavanshi, Sharad S. (Journal of Materials Science-Materials in Electronics, 2023)
Nature is a perfect laboratory for creating novel nanomaterials for a variety of applications. A robust green synthesis approach to GO-loaded Ag/ZnO nanocomposite materials using medicinal plant extraction and their potential application in methyl orange dye degradation are reported. The straightforward technique employs zinc and silver nitrate precursors in an aqueous solution of medicinal plant extract, causing the precipitation process. Prior to photocatalytic investigations, the physico-chemical properties of the material are analysed using TG-DTA, XRD, FE-SEM, TEM, EDAX and BET. The developed material showcase hexagonal wurtzite structure of ZnO, with face-centered-cubic phase of Ag and AgCl. All the samples exhibit aggregated, irregular rounded grains, as expected in the precipitation synthesis process. Pristine ZnO showed 15.5% degradation efficiency towards methyl orange, which was further improved by doping Ag from 0.5 to 2 mol%. The catalyst with 1 mol% Ag doping resulted in the better photocatalytic activity (26.30%), which has again improved by loading the GO (27.46%). The outcome of this study provides the new insights to GO-loaded Ag/ZnO nanocomposites by green synthesis route, in view of photocatalytic applications.